Enhancing the financial stability of families by promoting knowledge and planning in Islamic finance - Martini Dwi Pusparini; Fajar Fandi Atmaja; Ahmad Rifki Hidayat; Fachrina Fiddareini; Zein Muhammad Fachri (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Covid-19 pandemic has brought attention to the importance of family resilience, particularly in economic aspects. Family financial planning plays a crucial role in establishing resilience during times of crisis. This community service program seeks to enhance financial literacy and promote Islamic financial planning among mothers who are responsible for managing family finances. The approach involves engaging in interactive discussions, Q&A sessions, and practical exercises. Topics covered include financial assessments, managing cash flow, creating emergency funds, handling social contributions, understanding the Islamic perspective on wealth, planning for education and healthcare expenses, and implementing ZISWAF (Zakat, Infaq, Sadaqah, and Waqf). The outcome of this service is to foster comprehension and application of Islamic financial planning within families.